The Effect of Burnout, Work Experience, and Work Motivation on Employee Performance with Emotional Intelligence as Variable Moderation - Rosita, Rosita; RS, Tantri Yanuar (Universitas 17 Agustus 1945 Jakarta, 2019)
Performance is an important benchmark in the process of employee development and greatly affects the achievement of the organization as a whole. Performance may decline because of the high burnout. High motivation tends to be a maximum performance as well as work experience also influence performance as related to length of service and level of knowledge. In addition, the performance was also affected by emotional intelligence takes an important role to help people in dealing with problems in life. This study is aimed to determine the effect of burnout, work experience, and motivation to work on performance with emotional intelligence as a moderating variable. The method used is quantitative by collecting data using questionnaires and analyzing by moderated regression analysis (MRA). The sampling technique uses convenience sampling. The results show the accepted hypothesis is burnout affects the performance and motivation affects the performance while the rejected hypothesis is high emotional intelligence will reduce the effect of burnout on performance, high work experience will improve the performance. High emotional intelligence will increase the effect of work experience towards the employee performance, and high emotional intelligence will increase the effect of work motivation towards the employee performance.